Doctor-patient relationship in the light of the syari'ah: excerpts from the Fiqh Muamalat in Medicine Workshop 2013 - Sharifudin, Mohd Ariff; Wan Husin, Wan Rumaizi; Mohd Yusof, Nazri; Che Ahmad, Aminudin; Khan, Ed Simor; Awang, Mohd Shukrimi; Taib, Mai Nurul Ashikin (2013)
Medical practitioners are regarded as one of the noble professions in society. Muslim medical practitioners are bound to the rulings of the syari'ah, even in providing health services. Most discussions related to doctor-patient relationship focused on codes of conducts such as medical ethics, professionalism, and confidentiality. These were debated topics during the recent Fiqh Muamalat in Medicine Workshop. In this brief review, we would like to highlight more on the models of doctor-patient relationship and the syari'ah rulings related to it. The syari'ah rulings were reviewed from various aspects pertaining to the patient who seeks for treatments, the doctor who provides the medical services or treatment, involvement of a third party, and the form of agreement involving all related parties. The rulings were derived from the five basic rules pertaining to the actions and interactions of a person (al-ahkam al-taklifiyyah). Relationship models were classified based on the profitability of the service rendered, types of contract involved, as well as the related syari'ah rulings. The obligation of becoming a medical practitioner varies depending on various factors. Similarly, the rulings on patients seeking for treatment for medical illnesses remain debatable among scholars. Models of doctor-patient relationship can be summarized into four models; Model A - Charitable Work, Model B - Profit-based, Model C - Civil Servant, and Model D - Private Employee. Providing medical services is indeed a noble obligation. However, it involves certain requirements and rulings that may differ from what are commonly practiced.